Tinjauan Yuridis Terhadap Tindak Pidana Penipuan Online - Ama, Jefrianus Tamo; Kadir, Syukron Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The crime of online fraud is regulated in Law no. 11 of 2008 regarding amendments to Law no. 19 of 2016 concerning Informatics and electronic transactions. Online fraud is a criminal case that is categorized as a criminal offense. The problem of online fraud has existed since the development of technological tools. Fraud is classified as a criminal act because it is regulated in the Criminal Code which is classified as public law, and if it is violated. And if the elements of a criminal act of fraud are met then criminal sanctions can be applied according to Article 28 (1) of the ITE Law. The crime of fraud is regulated in CHAPTER XXV Book II of the Criminal Code which contains various forms of fraud which have their own special names. What is known as fraud is a crime that is formulated in articles 378 to 395. The conditions for an act to be considered a criminal act of fraud are that the act must fulfill all the elements that constitute a prohibited formula which is punishable by criminal law and the act must be against the law (no justification), in other words someone who is said to have violated the law must fulfill the elements contained in the Criminal Code.